Corrosion behaviour of stainless steels and a single crystal superalloy in a ternary LiCl–KCl–CsCl molten salt. (January 2015) - Hofmeister, M.; Klein, L.; Miran, H.; Rettig, R.; Virtanen, S.; Singer, R.F.
Highlights: Corrosion behaviour of different materials was tested in a fused LiCl–KCl–CsCl salt. The low-carbon steel showed intergranular corrosion for all testing conditions. The Ti-stabilised steel was protected up to about 500 °C and short exposure times. The Ni-base superalloy (CMSX-4) showed superior corrosion properties at 800 °C. Regarding corrosion, liquid salt cooling is feasible for Directional Solidification of superalloys. Abstract: In the present work, the corrosion properties of a low-carbon stainless steel (X2CrNi18–9) and a Ti-stabilised high-carbon stainless steel (X6CrNiTi18–10) were investigated in a molten LiCl–KCl–CsCl salt at 400, 500, and 600 °C for 1, 3, 9 and 27 h. In addition, a Ni-based superalloy (CMSX-4) was tested at 800 °C for 3 h. The low-carbon steel revealed severe intergranular corrosion for all testing conditions, whereas the Ti-stabilised steel was protected against intergranular corrosion by a Cr2 O3 passive layer for short exposure times and up to a temperature of approximately 500 °C. In comparison, CMSX-4 revealed superior corrosion resistance.